Perception of Cyber Threats Affects the Cyber Security Awareness Of the Population in Bangkok - Chowsil, Prasop; Chuacharoen, Orathai (MCU Haripunchai Review, 2025)
This research aimed to 1) examine the perception of cyber threats and cybersecurity awareness among the population in Bangkok 2) compare cybersecurity awareness classified by personal factors 3) investigate the relationship between the perception of cyber threats and cybersecurity awareness among the population in Bangkok The research employed a quantitative approach with a sample of 403 individuals residing in Bangkok. Data were collected using a questionnaire and analyzed using descriptive statistics and inferential statistics, including t-test, one-way ANOVA, LSD post hoc comparisons, and multiple regression analysis to test the hypotheses. The research results revealed that: 1) The overall perception of cyber threats and cybersecurity awareness among the population in Bangkok was at a moderate level, whereas overall cybersecurity awareness was at a high level. 2) In comparing cybersecurity awareness across personal factors, gender differences were not associated with significant differences in cybersecurity awareness, while age, education level, and occupation exhibited significant differences. 3) Regarding the relationship between the perception of cyber threats and cybersecurity awareness, two aspects of cyber threat perception—knowledge of cyber threats and cybersecurity training—were found to significantly influence cybersecurity awareness at the 0.05 significance level.